The Research and Application of Improved Search Method Based on Big Data. Issue 4 (December 2018) - Liu, Xiaozhao
Abstract: This paper improved an efficient search method to the problem of low efficiency for large data questions. Using shared history query results as a set of intermediate results, when a new query request arrives, analyze query request, provide keywords for user to choose and pick maser word and secondary word up. Master word match for historical inquiry is directly added to the matching portion of the historical results for directly as part of the new query result of the request if achieving matching. It can reduce the large number of double counting query history, save search time and improve query efficiency. By experimental comparison and analysis shows that big data based on improved query methods on can improve query efficiency.